The Development of English Speaking Proficiency to Increase Students’ Communication Skill in A Business and Technology College - Rani Ligar Fitriani (KOMVERSAL, 2022)
English speaking proficiency is very important to participate in the wider world of work. The speaking proficiency is measured in terms of the ability to carry out a conversation in the language. To improve English speaking proficiency, It ought not to be handiest within the study room however also, it's far a crucial a part of language mastering procedure out of it as students want more exposures, engagement, and assist from which they can research. The students need to accustom themselves to apply English. They need support from the environment to improve and develop their English especially speaking proficiency. This studies is achieved through a case study. This research is performed on the students of the second grade of LP3I Business and Technology College Tasikmalaya in the academic year of 2014-2015. The goal of this research is to discover: (1) the development of English speaking proficiency in LP3I Tasikmalaya Business and Technology College Tasikmalaya; (2) the hassle of developing English speaking proficiency programs in a business and technology college; and (3) the impact of developing English speaking program to the students’ English speaking proficiency at LP3I Business and Technology College Tasikmalaya. The respondents of this studies are ten college students and four English instructors which might be selected by using the usage of the purposive sampling method. The studies statistics are received from commentary, interviews, and document analysis. They are analysed by using three steps, particularly the data reduction, the data presentation/display and the conclusion drawing/verification. LP3I Tasikmalaya has its personal machine which includes some interrelated programs to broaden English skills in fashionable and speaking especially. The result of the research findings leads to the conclusion that: (1) LP3I Tasikmalaya has its own system which consists of some interrelated programs to develop English proficiency in general and to speak in particular. There are English programs that contribute to the development of students’ English speaking proficiency. English activities inside the lecture class foster the students to apply English in the right way to communicate. English activities outside the lecture class create the English atmosphere and accustom the students to speak English by by way of training extra within the English environment. (2) There are some issues in developing students’ English speaking skill at LP3I Tasikmalaya; The students’ difficulties to speak come from psychological factors (confidence, anxiety, motivation, awareness); The students’ difficulties in speaking come from the linguistic factors (pronunciation, vocabulary, grammar, fluency, comprehension). (3) There are some superb consequences of developing English speaking programs at LP3I Tasikmalaya to the students’ English speaking skill along with students’ confidence, students motivation, students awareness, college students vocabulary, college students initiative, college students pronunciation, and students’ comprehension in speaking English are enhancing